2000
DOI: 10.1038/sj.ijo.0801303
|View full text |Cite
|
Sign up to set email alerts
|

Increased response of cortisol and ACTH to corticotrophin releasing hormone in centrally obese men, but not in post-menopausal women

Abstract: There is evidence for enhanced hypothalamo ± pituitary ± adrenal axis (HPAA) activity in centrally obese premenopausal women. This has led to the hypothesis that increased cortisol production rates may be an aetiological factor in the genesis of central obesity. However, the relationship of obesity and body fat distribution to HPAA activity in men and postmenopausal women has not been established. We carried out CRH tests in 13 men and 8 post-menopausal women. We measured 24 h urine cortisol metabolites prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Previous reports suggest variously that BMI does not predict (53), predicts decreased (33,67,70), and predicts increased (1,20,23,68,76) cortisol concentrations, production and/or metabolism. The current analyses show that higher BMI in men is associated with lower calculated ACTH potency (higher ED 50 ), but no difference in 24-h cortisol secretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports suggest variously that BMI does not predict (53), predicts decreased (33,67,70), and predicts increased (1,20,23,68,76) cortisol concentrations, production and/or metabolism. The current analyses show that higher BMI in men is associated with lower calculated ACTH potency (higher ED 50 ), but no difference in 24-h cortisol secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other studies have reported no age or sex effects (19,29,32,46,48,53). Certain of these discrepancies could be due to ethnicity differences (14,80), time-of-day effects (72), measurement of cortisol in plasma, saliva, or urine (41,43,58), nature of stressor (54,71), basal vs. stressed states (2,81), concurrent obesity (1,23,33,67,68,70), estrogen use (46), stage of menstrual cycle (40), dietary carbohydrate intake (65), and potential sex-by-age interactions (78). The last consideration has been assessed in untreated children (28) and in adults following sequential dexamethasone/CRH exposure (30).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…It is unclear why the bidirectional effect of work stress was not seen among the women. There are apparent sex differences in physiological responses to experimental and real-life stressors [24][25][26][27][28] and the links between secretion of cortisol (a stress hormone) and central adiposity varied between men and women in a Whitehall II subsample study. 26 These sex differences are potential contributors to our findings, though small scale studies do not report consistent differences in stress eating patterns between men and women.…”
Section: Work Stress and Bmimentioning
confidence: 99%
“…18,22 On the other hand, chronic stress may also trigger physiological processes which lead to weight loss, 20,23 in particular, among individuals for whom chronic work stress is associated with suppressed appetite and increased physical activity. 18 As sex is a factor that appears to confer differential sensitivity to stress and may also affect choice of coping strategy, [24][25][26][27][28] it is important to examine stress effects on eating and weight change separately for men and women. In this report from the Whitehall II study, we examined the association between work stress and BMI with particular attention to the hypothesis that chronic work stress may induce weight gain in some individuals but weight loss in others.…”
Section: Introductionmentioning
confidence: 99%